EFFICACY OF INTRAVENOUS LIGNOCAIN VS SEVOFLURANE IN PREVENTION OF COUGHING AND DESATURATION AT EXTUBATION IN CHILDREN - Khattak, Rabnawaz; Haq, Inam ul; Abbasi, Tariq; Ahmad, Asrar; Khan, Shoaib Ahmed; Raja, Mushtaq Hussain; Khan, Safdar Ali (Journal of Ayub Medical College Abbottabad, 2018)
Background: Inadvertent coughing and desaturation are the most commonly faced and feared respiratory complications in post-anaesthesia period. The study was done to compare the efficacy of intravenous lignocaine versus sevoflurane in prevention of coughing and desaturation at extubation in children less than 6 years of age. Methods: This Randomized Control Trial was carried out from May 2013 to May 2016, at Combined Military Hospital Nowshera after obtaining approval from the hospital ethics committee (IREC-0003/5/13/Aneas). Children aged three months to six years undergoing surgical procedures requiring the placement of definitive airway were randomly assigned into two groups. Patients were anaesthetized by standardized balanced anaesthesia technique. In Group A (n=355), three minutes prior to extubation lignocaine 2% was used intravenously. In Group B (n=355), isoflurane was switched off, breathing circuit changed and sevoflurane started at minimum alveolar concentration (MAC 3-4%) for 3 minutes prior to extubation. Assessment for extubation was clinical. Oxygen saturation and severity of coughing were noted for 5 consecutive minutes, after extubation. Results: In group-A, 156 patients were less than 2 years of age while in group-B, 135 patients were less than 2 years old. In group-A, 199 and in group-B, 220 children were 2-6 years of age respectively. Post stratification the p-value for weight was 0.17 (p-value >0.05) and t-statistic was 1.36. Post stratification p-value for gender was 0.12 (p-value>0.05) and chi square statistic was 2.49. Group A had more eventful extubation with 270 cases of cough (76%) as compared to group-B where it was noted in 199 cases (56%). Similarly, desaturation was observed in 85 cases in group-A (24%) as compared to 28 cases (8%) in group-B. The difference between the groups was statistically significant. Conclusion: Sevoflurane based anaesthetic vapours mixture causes statistical significant prevention from events like coughing episodes and desaturation in post-extubation in children less than six years of age undergoing elective surgery. Keywords: intravenous lignocaine (IV); sevoflurane; laryngospasm; post extubation